Synthesis and characterisation of bis(2 methyl-8-hydroxyquinoline) zinc nanoparticles for organic light emitting diode applications. Issue 10 (3rd July 2019) - Suchitra, J.P.; Kala, A.; Sagadevan, Suresh; Bharathi Devi, V.; Podder, Jiban
ABSTRACT: In this paper, bis(2 methyl-8-hydroxyquinoline) zinc (Zn(mq)2 ) nanoparticles were synthesised at room temperature by a simple chemical precipitation method. The Zn(mq)2 nanoparticles were characterised by powder X-ray diffraction (PXRD) analysis to confirm the crystalline nature of the Zn(mq)2 nanoparticles. The morphology and the elemental composition of Zn (mq)2 nanoparticles were analysed by high-resolution scanning electron microscopy (HR-SEM) and energy dispersive X-ray analysis (EDAX). The functional groups of the compound were studied with the help of Fourier transform infrared spectroscopy (FTIR) and FT Raman spectroscopy. Further, Zn (mq)2 nanoparticles were characterised by C-13 NMR spectroscopy, mass spectroscopy and CHN analysis. The thermal stability of the particles was studied using TG-DSC curve. The optical properties of the particles were studied by means of UV–Visible spectroscopy. The luminescence property of the synthesised particles was observed from the photoluminescence spectrum to confirm the possible application in organic light emitting diode.